Pemikiran Politik Soetan Sjahrir - Cut Junianty Syahra (Dinamika Politik, 2012)
This is study about the analysis of the political thought of Soetan Sjahrir. The focus discusses about what causes Soetan Sjahrir reject the ideology of communism and fascism. The finding of this study is there are three important things to be the main cause why Soetan Sjahrir opposing the ideology of communism and fascism. First, in the ideology of communism contains the suppressions of the value of human freedom, either in political, social, and economic in the name of class struggle. Second, in the ideology of fascism contained the values that assume that a certain race is better than the other race. Third, because Soetan Sjahrir was an adherent of the ideology of democratic socialism that upholds human values, social justice and based on the principle of people sovereignty. The method that used is descriptive-qualitative method that intends to describe an event in more detail.Key Word: Communism, fascism, democratic socialism.